2016
DOI: 10.5812/numonthly.33180
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Antioxidant Effects of Withania coagulans Extract on Benign Prostatic Hyperplasia in Rats

Abstract: Background:Benign prostate hyperplasia (BPH) is a common urological disorder in elderly men. Phytotherapy is frequently used to alleviate the symptoms of this condition.Objectives:The present study investigated the effect of Withania coagulans extract (WCE), which is known to have antioxidant, anti-inflammatory, antihyperglycemic, and anti-cancer properties, on testosterone-induced BPH in rats.Materials and Methods:Forty Wistar rats were divided into five groups (each n = 8): the control group, the untreated B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 35 publications
(36 reference statements)
3
24
0
Order By: Relevance
“…A recent study showed that WCE increased the total antioxidant capacity (TAC) in benign prostatic hyperplasia in rats (36). These data are in line with the finding of our study indicating that pretreatment with WCE for 30 days improved the mean of SOD and CAT activity in WCE group when compared to I/R group.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study showed that WCE increased the total antioxidant capacity (TAC) in benign prostatic hyperplasia in rats (36). These data are in line with the finding of our study indicating that pretreatment with WCE for 30 days improved the mean of SOD and CAT activity in WCE group when compared to I/R group.…”
Section: Discussionsupporting
confidence: 82%
“…Antioxidant enzymes function as scavengers of free radicals by converting them to less harmful oxygen species [26]. Higher activities of antioxidant enzymes have an antioxidant effect by the alleviation of oxidative stress [7,25]. PFE treatment significantly the increased activities of antioxidant enzymes responsible for the reduction of oxidative damage in prostatic tissue induced by testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we showed that WC extract (WCE) improved the prostate antioxidant status and decreased the stromal cell proliferation in a rat BPH model (14). Our aim in the present study was to evaluate the effects of WCE on COX-2 expression and apoptosis in a rat model of BPH.…”
Section: Objectivesmentioning
confidence: 99%
“…Withania coagulans (WC) is a traditional medicine from the Solanaceae family that is used for the treatment of various health problems and diseases in South Asia and the southeast regions of Iran (13). WC is well known for its antioxidant, anti-inflammatory, antiproliferative, and anti-cancerous properties (14-16). It has been reported that Withaferin A, one of the bioactive components of Withania, induces apoptosis in prostate cancer cells (17).…”
Section: Introductionmentioning
confidence: 99%